1985
DOI: 10.1128/jcm.22.4.668-670.1985
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes of bovine astrovirus

Abstract: Three isolates of bovine astrovirus, one from the United Kingdom and two from the United States, possessed common antigens by immunofluorescence and strain-specific antigens by neutralization and were designated as two, and probably three, distinct serotypes. The isolate US2, despite being a different serotype, possessed the same restrictive cell tropism and cytopathology as previously reported for isolate US1, of the M cells of the dome epithelium of the Peyer's patches. Serotyping of 16 field isolates indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 8 publications
1
36
0
Order By: Relevance
“…Few documented antigenic classifications have been attempted for animal AstVs. Serological assays confirmed by molecular characterization, suggested the existence of a putative novel serotype of turkey astrovirus, TAstV-3 (Tang and Saif, 2004;Tang et al, 2005); similarly the application of cross-virus neutralization assays indicated the presence of more undefined serotypes of bovine AstV (Woode et al, 1985).…”
Section: Etiology and Taxonomymentioning
confidence: 90%
See 1 more Smart Citation
“…Few documented antigenic classifications have been attempted for animal AstVs. Serological assays confirmed by molecular characterization, suggested the existence of a putative novel serotype of turkey astrovirus, TAstV-3 (Tang and Saif, 2004;Tang et al, 2005); similarly the application of cross-virus neutralization assays indicated the presence of more undefined serotypes of bovine AstV (Woode et al, 1985).…”
Section: Etiology and Taxonomymentioning
confidence: 90%
“…Although a previous study suggested that BoAstV could be excreted by 60-100% of calves on farms (Bridger et al, 1984), only 5 out of 209 rectal swabs (2.4%) collected from asymptomatic adult cattle were found positive for BoAstV infection (Tse et al, 2011). In bovine, two serotypes have been recognized by serological investigation, namely BoAstV-1 and BoAstV-2 (Woode et al, 1985), and recent phylogenetic analyses support classification of BoAstVs and the newly discovered AstVs in roe deer (CcAstV) under the proposed ''genocluster GI'' of the Mamastrovirus (Bosch et al, 2010b;Smits et al, 2010;Tse et al, 2011). The antigenic diversity detected in the earlier studies is also reflected in the more recently described genetic diversity for BoAstV.…”
Section: Bovine Astrovirus (Boastv)mentioning
confidence: 94%
“…Since we found numerous positive samples which retested negative after an additional RNA extraction procedure, we can assume the viral load was low or the viral RNA too damaged, and additional thaw may have further damaged the RNA, to obtain better and longer sequence fragments. Human and several mammal (porcine, bovine) and avian astVs have been isolated and amplified in cell culture in order to provide a larger amount of high quality viral genetic material (Lee and Kurtz, 1981;Shimizu et al, 1990;Woode et al, 1985). To date, this technique has remained unsuccessful for bat astVs (De Benedictis et al, 2011), which may explain the limited number of available ORF2 references for bat astVs in GenBank.…”
Section: Discussionmentioning
confidence: 99%
“…These three isolates of bovine astrovirus were shown to possess a common antigen detected by immunofluorescence. However, as there was no cross-neutralization among the three isolates, it was concluded that there are at least two distinct serotypes and probably three: US1 serotype 1; US2 serotype 2; UK serotype 3 (Woode et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…They assumed that the particles possessing six-pointed star configuration and 28 nm in diameter were not pathogenic because transmission of the virus did not induce diarrhea in gnotobiotic calves. Later, two additional isolates of the virus (US1 and US2) were reported in the U.S.A. (Woode et al, 1984(Woode et al, ,1985. These three isolates of bovine astrovirus were shown to possess a common antigen detected by immunofluorescence.…”
Section: Introductionmentioning
confidence: 99%